Internal Digital Marketing Promotion Tourism in the Industrial Era 4.0 - Suidarma, I Made; Noviyanti, Ni Putu Ratih (Universitas Negeri Semarang, 2023)
Digital marketing has become aspect important in promotion tourism in the Industrial 4.0 era. Government tourism office Regency Badung as responsible institution answer on promotion tourism in the region, too adopt digital technology in effort increase Power pull destination they. Abstract This serve analysis about challenges and opportunities facing the Tourism Department Regency Badung in implement digital marketing for promote tourist they. Challenge the covers limitations source Power people and budgets, intense online competition, and change social media platform algorithms. However, through implementation of appropriate strategies, such as increase staff digital skills, creating engaging visual and interactive content, and it works The same with digital influencers, Tourism Department can overcome challenge the. In abstract this is also proposed For utilise technology, do careful data analysis, and interweaving partnership with platforms and actors business local For increase effectiveness digital campaign. With optimizing application of digital marketing, Tourism Department Regency Badung can increase visibility destination tourism, interesting more Lots candidate tourists, and strengthen image destination they as objective attractive tourism in the Industrial 4.0 era.